(untitled) (JURNAL ENFIT : Entomologi dan Fitopatologi, 2019)
The scope of this study is the management of insects that carry Ralstonia solanacearum Phylotype IV (the cause of banana blood disease). The objectives of this study were: (1) to identify insects in Kepok banana flowers, and (2) to identify insects in Kepok banana flowers that act as carriers of R. solanacearum Phylotype IV, and the population density of these bacteria is carried by each insect. The sampling of banana plantations was carried out based on pusposive sampling method. Insect collection uses modified insect nets, and insect collection uses modified insect nets, and insects are morphologically identified. This bacterial isolation was carried out based on the cup pour method on NA + TZC media. Inoculation of bacterial isolates was carried out by injection method on the tip of the old Kepok banana. The insect species of visitors to the banana flower in South Minahasa District were Oscinella sp., Aphis mellifera, Chelisoches morio, and Dolichoderus sp. All species of visitors to the Kepok banana flower in South Minahasa carry Ralstonia solanacearum Phylotype IV. Oscinella sp., A.mellifera, C.morio, and Dolichoderus sp. each carrying 17,636.39, 15,666.67, 113.33, and 2,400.00 CFU mL.